2016
DOI: 10.1038/srep34721
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Cronobacter sakazakii in powdered infant formula using an immunoliposome-based immunomagnetic concentration and separation assay

Abstract: This study aimed to optimize the applicability of an immunoliposome-based immunomagnetic concentration and separation assay to facilitate rapid detection of Cronobacter sakazakii in powdered infant formula (PIF). To determine the detection limit, specificity, and pre-enrichment incubation time (0, 4, 6, and 8 h), assay tests were performed with different cell numbers of C. sakazakii (2 × 100 and 2 × 101 CFU/ml) inoculated in 10 g of PIF. The assay was able to detect as few as 2 cells of C. sakazakii/10 g of PI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 49 publications
0
12
0
Order By: Relevance
“…The authors further demonstrated the potential of these liposomes in quantifying viral counts using real-time impedance measurements as well as their feasibility as a reliable platform for the determination of viral loads with an ability to detect pathogenic microbes and other bio-fragments ( Damhorst et al, 2013 ). In addition, these liposome-based methods for pathogen detection have been investigated by others ( Shukla et al, 2016a , b ; Song et al, 2016 ). Recently, attempts have been made to develop advanced liposome-based detection methods to achieve multiplexing and gain approval for commercial applications.…”
Section: Liposome Nanoparticles As Detection Sensor In Food Sectormentioning
confidence: 99%
See 1 more Smart Citation
“…The authors further demonstrated the potential of these liposomes in quantifying viral counts using real-time impedance measurements as well as their feasibility as a reliable platform for the determination of viral loads with an ability to detect pathogenic microbes and other bio-fragments ( Damhorst et al, 2013 ). In addition, these liposome-based methods for pathogen detection have been investigated by others ( Shukla et al, 2016a , b ; Song et al, 2016 ). Recently, attempts have been made to develop advanced liposome-based detection methods to achieve multiplexing and gain approval for commercial applications.…”
Section: Liposome Nanoparticles As Detection Sensor In Food Sectormentioning
confidence: 99%
“…However, since all liposome-based detection methods are based on fluorescence signals that differ according to various pathogenic bacteria, single-step multiple detection is a feasible target. Possible research result formats based on our earlier research were published by Shukla et al (2016a , b ).…”
Section: Liposome Nanoparticles As Detection Sensor In Food Sectormentioning
confidence: 99%
“…Cronobacter sakazakii (formerly Enterobacter sakazakii) is one of an opportunistic pathogen that can contaminate a wide range of foods and causes different disease like meningitis, necrotizing enterocolitis and bacteremia in immunocompromised, low weight individuals, neonates and infants with a mortality rate of 40-80% [1][2][3][4][5]. As Almajed and Forsythe [6] indicated in their research Cronobacter sakazakii clinical isolates are able to enough because of microbial cross-contamination like Cronobacter sakazakii [3,14,37,38]. The other contributing factors that lower the rate or early cessation of breastfeeding is that mothers might be informed not to breastfeed or the mother may take medication [34], or infants born from working-class mothers.…”
Section: Introductionmentioning
confidence: 99%
“…C. sakazakii has been implicated in severe forms of neonatal infection, such as bacteremia, meningitis, and necrotizing enterocolitis, particularly in infants and premature babies; the mortality rates associated with these bacteria range from 50 to 80% (Li et al, 2013). Powdered infant formula (PIF), which is a main source of nutrition for neonates and infants, has been recognized as the major vehicle of transmission of C. sakazakii , and the consumption of contaminated PIF is associated with the majority of C. sakazakii outbreaks (Shukla et al, 2016). Due to the role of trehalose accumulation within its cells, C. sakazakii is remarkably resistant to desiccation (Breeuwer et al, 2010).…”
Section: Introductionmentioning
confidence: 99%